2014
DOI: 10.1097/pcc.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Outcome of Diastolic Dysfunction in Children With Fluid Refractory Septic Shock—A Prospective Observational Study*

Abstract: Diastolic dysfunction is common in children with fluid refractory septic shock, and immediate outcomes may be poorer in such patients. Increased central venous pressure after initial fluid resuscitation may be an early indicator of diastolic dysfunction and warrant urgent bedside echocardiography to guide further management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
(74 reference statements)
4
32
0
Order By: Relevance
“…Sankar et al pointed out that the prevalence of left ventricular diastolic dysfunction among 56 children with fluid-refractory septic shock (3 months to 17 years of age) was as much as 41% with their mortality rate of 43% [41]. Raj et al also investigated 30 septic shock children and adolescents (1 month to 21 years of age) and showed that the prevalence of left ventricular systolic, diastolic, and both dysfunction was 37%, 33%, and 17%, respectively, [42].…”
Section: Hemodynamic Managementmentioning
confidence: 99%
“…Sankar et al pointed out that the prevalence of left ventricular diastolic dysfunction among 56 children with fluid-refractory septic shock (3 months to 17 years of age) was as much as 41% with their mortality rate of 43% [41]. Raj et al also investigated 30 septic shock children and adolescents (1 month to 21 years of age) and showed that the prevalence of left ventricular systolic, diastolic, and both dysfunction was 37%, 33%, and 17%, respectively, [42].…”
Section: Hemodynamic Managementmentioning
confidence: 99%
“…DBS is known to have an excitatory or inhibitory effect depending on stimulation frequency stimulation, although results tend to vary as a function of stimulation parameters and brain region under study (67-69), and biphasic cathode-first stimulation tends to be more effective in eliciting functional responses (70-72). In the present study, we tested different stimulation parameter combinations and selected biphasic pulse trains with 20 Hz frequency, ±8 V amplitude, 100μs pulse duration, 500 ms pulse train duration and 10s pulse trains intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Although many studies have commented on the left ventricular (LV) systolic function in patients with septic shock, diastolic function is often overlooked despite being a very important part of echocardiographic assessment in such patients, [14][15][16][17] The systolic function parameters were below the accepted normal cutoffs in 25%, 45%, and 15%, respectively, while diastolic dysfunction was seen in 12.5%. Overall, more than half (55%) had at least one echocardiographic parameter of myocardial dysfunction.…”
mentioning
confidence: 99%
“…Second, one needs to define which particular cardiac biomarker to study in patients with septic shock, viz., only CK-MB (as done in the current study) or troponins (as described in most of the previous reports), with the introduction of hs-cTn further enhancing diagnostic sensitivity. 7,10,17,18 An advantage of using multiple biomarkers is to be able to document if diverse markers (CK-MB, troponins, C-reactive protein, etc.) have differential release kinetics and develop cutoffs for them to predict outcomes.…”
mentioning
confidence: 99%